Inovasi Olahan Bayam Brazil Menjadi Kuliner Sehat Pada Kelompok Tani “Mekar Tani" Kabupaten Lima Puluh Kota - Indrayati, Sri; Laila, Wilda; Octafia, Sri Mona; Harleni, Harleni; Yensasnidar, Yensasnidar; Suryani, Suryani (Journal Of Human And Education (JAHE), 2024)
The “Mekar Tani” farmer group is one of the farmer groups located in Jorong Gando, Nagari Piobang, Payakumbuh District, Lima Puluh Kota Regency, West Sumatra Province, and has 20 members. Previously, this farmer group had received training activities on compost production skills, and received Brazilian spinach seeds from the activity to be developed. Now, this farmer group is actively cultivating Brazilian Spinach by utilizing their yard and some other vacant land. However, in terms of utilizing Brazilian spinach, the farmer group still utilizes Brazilian spinach as a vegetable or only as an ornamental plant. The group has not been able to process Brazilian spinach into healthy food processing innovations. Therefore, this effort is carried out in the form of mentoring in the form of skills training to develop processed Brazilian Spinach as a healthy culinary. The purpose of this activity is to expand partners' knowledge and skills in producing food products from Brazilian Spinach. The results of the activity showed an increase in partners' knowledge and skills in processing Brazilian spinach into processed healthy food increased from 36% to 85.5%. All training participants were very enthusiastic about participating in this training activity. Partners are determined to continue the production of healthy food from Brazilian spinach in the future so that they can be more skilled, and can increase group income.